Oral Transmucosal Delivery Systems: Exploring Innovative Dosage Forms, Current Industrial Applications and Regulatory View - Palem, Chinna Reddy; Rendla, Ravinder; Lekkala, Vamshi Krishna; Andhi, Neha; Nagamalli, Nishant Kumar; Battula, Deepthi; Gumudevelli, Sridhar (International Journal of Pharmaceutical Investigation, 2026)
Oral transmucosal drug delivery systems represent an innovative approach for the administration of therapeutic agents through the mucosal membranes, such as sublingual and buccal membranes in the mouth, offering advantages of rapid onset of action, bypass the first pass metabolism, and enhanced patient compliance. Current review explores the various dosage forms of oral transmucosal delivery, highlighting their unique formulations and delivery mechanisms. This review also discusses the cutting-edge technologies driving the development of transmucosal systems, such as mucoadhesive polymers, permeation enhancers, which improve bioavailability and therapeutic efficacy. Furthermore, the industrial applications of transmucosal drug delivery systems are examined in light of current market trends, with an emphasis on their use in pain management, hormone therapy, and emergency care. The review article also covers the regulatory challenges and commercialization of oral transmucosal products, detailing the impact of agencies such as the US FDA, Europe EMA and Central Drugs Standard Control Organization (CDSCO) on product development, and safety assessments. In conclusion, while oral transmucosal drug delivery systems have demonstrated significant potential, continued research, innovation, and regulatory clarity are required to fully harness their benefits in diverse therapeutic areas.
Keywords: Buccal Delivery; Mucoadhesive Polymers; Regulatory view; Sublingual; Transmucosal Drug Delivery